Determination of the Statistical Power of Fatigue Characteristics in Relation to the Number of Samples - Przemysław Strzelecki; Janusz Sempruch (Applied Sciences, 2024)
The paper presents guidelines included in the ISO 12107:2003 standard regarding the number of samples for determining the fatigue characteristics in the high cycle range. The proposed normative values were compared with the classical statistical approach. Fatigue test results for S355J2+C steel for rotary bending were used for verification. In addition, the error and power of a statistical test were determined for characteristics with different sample sizes. It determined the number of specimens to estimate the fatigue curve, which required significant error and power of the statistical test.